Gender divide is deep. - Hill, Paul (Times Higher Education Supplement, 2004)
Reports on the gender division in college courses in Great Britain. Tendency for female students to shun engineering and computer science courses; Academic performance of female students compared to their male counterparts; Statistical figures released by the Higher Education Statistics Agency regarding the homogeneity of college courses.